Development of a direct patterning method for functional oxide thin films using ultraviolet irradiation and hybrid-cluster gels and its application to thin-film transistor fabrication. (9th March 2018) - Yoshimoto, Yuuki; Li, Jinwang; Shimoda, Tatsuya
Abstract: A gel state exists in the solution–solid conversion process. We found that solidification can be promoted by irradiating the gel with ultraviolet (UV) light. In this study, a patterning method without using a vacuum system or employing photoresist materials has been proposed wherein solidification was applied to a gel by UV irradiation. Indium oxide gel, indium gallium oxide gel, lanthanum zirconium oxide gel, and lanthanum ruthenium oxide gels were successfully patterned by using our technique. Moreover, an oxide thin-film transistor was fabricated by our novel patterning method and was successfully operated.